Avaliação da viabilidade e desenvolvimento in vitro de oócitos de gatas domésticas após vitrificação em meio suplementado com vitamina E - Gutierrez, Raquel Ribeiro [UNESP] (2014)
The use of techniques of cryopreservation of gametes in domestic cats are considered important in enhancing procedures in assisted reproduction. Vitrification is based on the use of high concentrations of cryoprotectants in order to inhibit the formation of ice crystals. It is possible that cryopreservation induces the production of reactive oxygen species (ROS) or change the enzymatic antioxidant potential of the oocyte, so one might speculate that the addition of antioxidants to the means of vitrification could reduce the oxidative stress caused by cryoprotectants. In the first experiment are compared four protocols vitrification using as base medium (MB) the TCM199 (tissue culture medium 199) more antibiotic glucose plus cryoprotectants: G1 (EG + 3M ethylene glycol + 2M dimethyl-DMSO), G2 (3M EG + 3M 1,2 propanediol - PrOH) , G3 (1.5 M EG + 1M DMSO) and G4 (1.5 M EG + 1.5 M PrOH) . After thawing, the material was assessed for viability and morphological changes (staining cFDA / trypan blue). In this , there was no statistical difference (p = 0.2857) among the four groups thawed oocytes studied with respect to morphology, but in relation to oocyte viability G1 and G2 groups had a higher percentage of viable oocytes , but did not differ ( 35.71% and 36.84 %, respectively , p = 0.018). In the second experiment three concentrations of vitamin E (0.4 , 0.6 and 0.8 mM) were added to the protocol MB with 3M EG + 3M PrOH , L forming the groups G 0.4 mM, G 0.6 mM, G 0.8 mM and G 0 (no added vitamin E). The choice of the base protocol was in accordance with the results obtained in experiment I. We observed improvement in percentage (p = 0.0032) of oocytes with normal morphology in groups G 0.6 mM (88.6 %) and G 0.8 mM (62.5 %). Experiment II oocytes that maintained their morphology after thawing were subjected to in vitro maturation for a period of 36 hours. When evaluating the resumption of meiosis, we observed no statistical difference ...